PERCOBAAN PEMBUATAN PULP SULFAT DARI KAYU MAKADAMIA (MACADAMIA HILDEBRANDII VAN STEEN) - Rena M Siagian; Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Macadamia hildebrandii van Steen, commonly known as makadamia, belongs to the family Proteaceae. Until recently, this wood has not been widely used and only grown sporadically in several places in Indonesia mainly used for non commercial purposes. The wood material used in the. experiment was obtained from Sipangan Bolon, North Sumatra for both pulping trials and chemical analyses.The chemical constituents of the wood are typically of those tropical wood containing 46.6% cellulose, 24.6% of lignin, and relatively low 14.4% pentosan. The average specific gravity was 0.61 and the fibre length of 1.76 mm. The pulping experiment was conducted in laboratory digester employing 20% active alkali, 170°C maximum temperature wich was maintained for 120 minutes. The cooking sulfidity was made at 2 levels i.e. 25% and 30%.The makadamia pulp yield ranged from 32.4 to 34. 7% with low Permangante number 2.15 to 2. 64. The pulp strength was fair and comparable to those of the commercial types. By adding of anthraquinone catalyst at 0,1percent by weight of the wood material to cooking, a significant improvement in pulp strength was commenced. This is particular noticed when using 25% sulfidity during the pulping.